(untitled) (Journal of Hama University, 2023)
The study was carried out during the period between 2017 - 2021 AD and used 1108 records of Friesian cows in the two stations of Jub Ramleh and Vidio cows, with the aim of analyzing and evaluating the productive characteristics (actual milk quantity, 305 days of modified milk production, age at first calving, length of milk season). The data were classified, entered, and organized according to Excel, and subjected to the general linear model, and Duncan’s test was used to compare means according to the statistical program SPSS. The results of the study showed that the general average of the total milk quantity was 6216.92 kg, as it was 5560.77 and 6873.7 kg in Jub Ramla and Fido cows station, respectively. The results showed a significant effect of the station on total milk production, as the difference between the two stations was 1312.3 kg. The general average of the adjusted milk production was 5810.52 kg, as it was 5321.91 and 6299.13 kg in Jeb Ramla and Fido stations, respectively. The results showed a significant effect of the two plants on the production of modified milk. The cows bred in Jub Ramla station had the highest mean age at first calving, which was 26.66 months, compared to those bred in Fido station, which achieved the lowest average age at first calving, which was 25.83 months. The average length of milking period was 327.66 and 380.82 days for Jub Ramla and Fido cow station, respectively. The differences were highly significant between the studied stations for the length of the season, as the difference between the two stations was 53.16 days. It is concluded that the productivity indicators of Friesian cows in the two studied stations were equal or higher than their counterparts in developing countries and in countries with similar environmental conditions to Syria, but lower than those of cows of the same breed in the country of origin, and this is mainly due to the difference in environmental conditions, and methods of care, and management